A time‐lagged association between the gut microbiome, nestling weight and nestling survival in wild great tits. Issue 4 (9th February 2021) - Davidson, Gabrielle L.; Somers, Shane E.; Wiley, Niamh; Johnson, Crystal N.; Reichert, Michael S.; Ross, R. Paul; Stanton, Catherine; Quinn, John L.
Abstract: Natal body mass is a key predictor of viability and fitness in many animals. While variation in body mass and therefore juvenile viability may be explained by genetic and environmental factors, emerging evidence points to the gut microbiota as an important factor influencing host health. The gut microbiota is known to change during development, but it remains unclear whether the microbiome predicts fitness, and if it does, at which developmental stage it affects fitness traits. We collected data on two traits associated with fitness in wild nestling great tits Parus major : weight and survival to fledging. We characterised the gut microbiome using 16S rRNA sequencing from nestling faeces and investigated temporal associations between the gut microbiome and fitness traits across development at Day‐8 (D8) and Day‐15 (D15) post‐hatching. We also explored whether particular microbial taxa were 'indicator species' that reflected whether nestlings survived or not. There was no link between mass and microbial diversity on D8 or D15. However, we detected a time‐lagged relationship where weight at D15 was negatively associated with the microbial diversity at D8, controlling for weight at D8, therefore reflecting relative weight gain over the intervening period. Indicator species analysis revealed that specificity values were high and fidelity values were low, suggesting that indicator taxa were primarily detected within either the survived or not survived groups, but not always detected in birds that either survived or died. Therefore these indicator taxa may be sufficient, but not necessary for determining either survival or mortality, perhaps owing to functional overlap in microbiota. We highlight that measuring microbiome‐fitness relationships at just one time point may be misleading, especially early in life. Instead, microbial‐host fitness effects may be best investigated longitudinally to detect critical development windows for key microbiota and host traits associated with neonatal weight. Our findings should inform future hypothesis testing to pinpoint which features of the gut microbial community impact on host fitness, and when during development this occurs. Such confirmatory research will shed light on population level processes and could have the potential to support conservation. Abstract : Emerging evidence points to the gut microbiota as an important factor influencing host health. In wild birds, the authors show that a less diverse microbiota early in development is associated with larger‐than expected weight at a later development stage. They highlight several indicator taxa influencing nestling survival for further confirmatory research.